2013
DOI: 10.1161/strokeaha.112.675462
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Neuroprotection by Local Intra-Arterial Infusion of Human Albumin Solution and Local Hypothermia

Abstract: The local low-dose cold albumin infusion into the ischemic area offered a combination of regional brain hypothermia and albumin administration, which enhanced neuroprotection and would be beneficial in the clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 13 publications
3
41
0
1
Order By: Relevance
“…The present study demonstrated that transarterial regional hypothermia exerts robust neuroprotective effects in the pMCAO with tCHP model, as well as the typical tMCAO model, as reported previously (Chen et al, 2013;Ding et al, 2003;Ding et al, 2004a;Ding et al, 2004b;Kurisu et al, 2015;Luan et al, 2004;Zhao et al, 2009). This therapy significantly improved neurological deficits and decreased infarct/edema volumes.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The present study demonstrated that transarterial regional hypothermia exerts robust neuroprotective effects in the pMCAO with tCHP model, as well as the typical tMCAO model, as reported previously (Chen et al, 2013;Ding et al, 2003;Ding et al, 2004a;Ding et al, 2004b;Kurisu et al, 2015;Luan et al, 2004;Zhao et al, 2009). This therapy significantly improved neurological deficits and decreased infarct/edema volumes.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with previous findings (Chen et al, 2013;Ding et al, 2003;Ding et al, 2004a;Ding et al, 2004b;Luan et al, 2004;Zhao et al, 2009), we also clarified that transarterial regional hypothermia exerts strong neuroprotective effects on ischemia-reperfusion (I/R) injury (Kurisu et al, 2015). However, the effects of this therapy have only been examined in a typical ischemic stroke model, the transient middle cerebral artery occlusion (tMCAO) model (Chen et al, 2013;Ding et al, 2003;Ding et al, 2004a;Ding et al, 2004b;Kurisu et al, 2015;Luan et al, 2004;Zhao et al, 2009), which is a complete reperfusion model (Fluri et al, 2015;Takahashi et al, 2012;Zhao and Steinberg, 2011). The effects of this therapy have not yet been investigated in other ischemic stroke models, even though ischemic stroke in humans is extremely diverse in its pattern of occlusion and reperfusion in actual clinical settings.…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…Preliminary studies using LEVI with neuroprotective drugs have shown exceptional promise; a 2012 study by Song et al found that LEVI of a magnesium sulfate solution at 15°C caused a 65% reduction in infarct volumes compared to a 48% reduction from LEVI alone [51]. Similar results were found following LEVI of a 20% human albumin solution cooled to 0°C [52]. Normothermic local infusion of drugs has shown potential as well, as LEVI of erythropoietin at room temperature reduced infarct volumes by 21% (signiicant compared to control), decreased apoptosis in the ischemic core and penumbra, and signiicantly preserved neurological scores [53].…”
Section: Drug Delivery Into Ischemic Territory Through Levimentioning
confidence: 88%
“…Serum albumin is a unique multifunctional protein and has been shown to be neuroprotective [2][3][4][5][6]. Several studies have demonstrated the obvious protective influence of serum albumin in many diseases, such as myocardial infarction and cardiovascular diseases [7][8][9].…”
Section: Introductionmentioning
confidence: 99%